Missing a Nurse Visit - Miriam Wüst; Jonas Lau-Jensen Hirani; Hans Henrik Sievertsen (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2021)
This paper studies the impact of the timing of early-life investment policies on child and maternal health. We exploit variation induced by a 2008 Danish nurse strike that resulted in a large-scale cancellation of home visits for families with infants. Combining unique nurse records with administrative data, we show that missing the first but not later visits increases child and mother contacts to health professionals and the probability of maternal mental health issues. We show that likely mechanisms for these results include nurses' focus on timely maternal mental health screening and information provision to new families.
Keywords: I11; I12; I14; I18; I21; 330; early-life health; early interventions; nurse home visiting; parental investments